DARI ‘NEGARA ISLAM’ KE POLITIK DEMOKRATIS: WACANA DAN ARTIKULASI GERAKAN ISLAM DI MESIR DAN INDONESIA FROM ‘ISLAMIC STATE’ TO DEMOCRATIC POLITICS: DISCOURSES AND ARTICULATIONS OF ISLAMIST MOVEMENT IN EGYPT AND INDONESIA - Umar, Ahmad Rizky Mardhatillah (P2KK LIPI, 2016)
Abstract This article aims to explain discourses and articulations of Islamist movements in Egypt and Indonesia. In Egypt, the Muslim Brotherhood has emerged as one of the most important political force following the regime change in 2011. They have succeeded in installing Mohammad Morsy and Freedom and Justice Party in power after winning the 2012 General Elections. In Indonesia, the Prosperous and Justice Party (PKS) has also emerged as one of strong political parties following 1998 Reformasi, even though their success was not as visible as the Muslim Brotherhood. By using post-foundationalist approach, this article attempts to provide an explanation of discourses and articulations of both movements in the political arena. Having traced the historical-political trajectory of Islamist movements in Egypt and Indonesia, this article argues that both Islamist movements have departed from a universalist conception of ‘Islam’ that aims to politically articulates Islam as a basis of the state. This article also finds that there have been different achievements of these attempts in Egypt and Indonesia, due to strategies, articulations, and negotiation with other political forces in each states. Keywords: Islamism, Egypt, Indonesia, discourses, articulations, Post-foundationalism Abstrak Artikel ini bertujuan untuk menjelaskan wacana dan artikulasi gerakan Islam di Mesir dan Indonesia. Di Mesir, Al-Ikhwan al-Muslimun telah menjelma menjadi sebuah kekuatan politik terpenting setelah pergantian rezim pada tahun 2011. Mereka telah berhasil menempatkan Mohammad Morsy dan Partai Keadilan Pembangunan dalam kekuasaan setelah memenangi Pemilu 2012. Di Indonesia, Partai Keadilan Sejahtera juga menjelma sebagai kekuatan politik setelah Reformasi 1998, walaupun kesuksesan mereka tak sebesar Ikhwan. Dengan menggunakan pendekatan post-fondasionalis, artikel ini berupaya untuk menyediakan penjelasan tentang bagaimana wacana dan artikulasi Gerakan Islam di kedua negara tersebut diproduksi setelah pergantian rezim. Dengan melacak perjalanan politik dan sejarah Gerakan Islam di Mesir dan Indonesia, artikel ini berargumen bahwa kedua Gerakan Islam di Mesir dan Indonesia berangkat dari konsepsi universalis tentang Islam yang bertujuan untuk menjadikan Islam sebagai dasar negara. Secara garis besar, artikel ini menemukan bahwa ada perbedaan hasil yang diperoleh Gerakan Islam di dua negara tersebut, yang antara lain dipengaruhi oleh perbedaan strategi, artikulasi, dan negosiasi dengan kekuatan politik lain di negara tersebut. Kata kunci: Islamisme, Mesir, Indonesia, wacana, artikulasi, Post-fondasionalisme